Pilot study on comparative assessment of facial profile changes using photographic images and cephalometric radiographs: a pre and post-orthodontic treatment analysis (Journal of Face Aesthetics, 2023)
Aim. This study aimed to compare changes in facial profile as assessed by photographic images and cephalometric radiographs, before and after orthodontic treatment, and evaluate the feasibility of substituting cephalometric radiographs with photographs in the post‑treatment assessment of facial profile.Material and methods. Thirteen patients receiving orthodontic treatment at the Department of Maxillofacial Orthopedics and Orthodontics at the Medical University of Poznan were included. Photographic and radiographic documentation including lateral cephalometric radiographs and profile photographs, both pre and post‑treatment, were analyzed. Various angles and distances were measured to assess changes in the facial profile. Statistical analyses were performed using Statistica v.13 software.Results. Significant changes were noted in several parameters when comparing pre and post‑treatment records. These changes varied depending on whether the assessment was conducted using photographs or cephalometric radiographs. While photographs revealed visible changes in the facial profile, key skeletal and dental information could only be ascertained through cephalometric analysis.Conclusion. Although photographs are valuable for tracking visible changes and patient communication, their limitations for precise measurements and inherent variability hinder their standalone use for post‑treatment assessment. Our findings underline the continued importance of cephalometric radiographs in comprehensive orthodontic assessment. Further research with larger cohorts is necessary to validate these results and further explore this area of orthodontic study.
Keywords: orthodontic treatment; facial profile; cephalometric radiograph; photographic images; profile changes